Correlation of Serum 25(OH) Vitamin D Levels With TNF-α and Caspase Levels in Sjögren`s Syndrome Patients - Susanto, Agus Joko; Sunggoro, Agus Jati; Wati, Fatna Andika (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Vitamin D deficiency is known to cause changes in disease pathogenesis in primary Sjögren's syndrome related to its immunological effects. Objective: This study aims to determine the correlation between serum 25(OH) vitamin D levels and TNF-α and caspase levels in Sjögren's syndrome patients. Methods: This study was a cross-sectional study involving 34 Sjögren's syndrome patients aged 18-59 years with vitamin D deficiency/insufficiency and measured levels of TNF-α and caspase. Result: The correlation between 25(OH) vitamin D levels and caspase levels obtained a value of r=-0.581, which means that there is a negative correlation in the moderate category (r=0.400-0.599) between 25(OH) vitamin D levels and caspase levels, and the p-value =<0.001 (p-value<0.05). The correlation between 25(OH) vitamin D levels and TNF-α levels obtained a value of r=-0.436, which means that there is a negative correlation in the moderate category (r=0.400-0.599) between 25(OH) vitamin D levels and a decrease in TNF-α, and p-value =<0.001 (p-value<0.05). Conclusion: There was a significant negative relationship between 25(OH) vitamin D levels and TNF-α and caspase levels.